2017
DOI: 10.3233/jad-161222
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Cerebral Blood Flow in Mild Cognitive Impairment Assessed Using Phase-Contrast MRI

Abstract: There is increasing evidence of a vascular contribution to Alzheimer's disease (AD). In some cases, prior work suggests that chronic brain hypoperfusion could play a prime pathogenic role contributing to the accumulation of amyloid-β,while other studies favor the hypothesis that vascular dysfunction and amyloid pathology are independent, although synergistic, mechanisms contributing to cognitive impairment. Vascular dysfunction can be evaluated by assessing cerebral blood flow impairment. Phase contrast veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 50 publications
3
20
0
Order By: Relevance
“…Cerebral blood flow is also important for maintaining proper brain perfusion. Chronically low cerebral blood flow has been reported to contribute to cognitive decline and dementia in older adults,52116117118 and has been associated with autism in children 119. The increases in cerebral blood flow and oxygen metabolism in children consuming NEWSUP, especially those consuming at least 75% of their supplement, suggest changes in brain health that could be either a cause or a consequence of improved cognitive function 22120121122123124.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral blood flow is also important for maintaining proper brain perfusion. Chronically low cerebral blood flow has been reported to contribute to cognitive decline and dementia in older adults,52116117118 and has been associated with autism in children 119. The increases in cerebral blood flow and oxygen metabolism in children consuming NEWSUP, especially those consuming at least 75% of their supplement, suggest changes in brain health that could be either a cause or a consequence of improved cognitive function 22120121122123124.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only two studies have explored the differences in CBF between individuals with SCD and HCs. According to Hays et al, patients with SCD exhibited lower CBF in the medial orbitofrontal cortex and higher CBF in the right putamen than HCs [ 162 ], while de Eulate et al did not observe any differences in total blood flow between individuals with SCD and HCs [ 163 ].…”
Section: Functional Mrimentioning
confidence: 99%
“… Viviano et al, (2019) [ 115 ] 2 binary questions rs-fMRI Cross-sectional NC: n = 48 (66.96 ± 8.79) SCD: n = 35 (68.51 ± 7.66) SCD showed lower average FC. Eulate el al., (2017) [ 163 ] Memory clinic consultation ASL Cross-sectional NC: n = 32 (72.3 ± 5.6) SCD: n = 28 (67.3 ± 7.8) MCI: n = 34 (73.7 ± 7.5) AD: n = 21 (75.8 ± 6.2) No differences in CBF between SCD and HC. Hays et al, (2018) [ 162 ] Memory clinic consultation ASL Cross-sectional NC: n = 35 (73 ± 6.25) SCD: n = 35 (72.54 ± 5.07) SCD showed negative associations between verbal memory and CBF.…”
Section: Functional Mrimentioning
confidence: 99%
“…A strength of our study is the relatively large sample size in each diagnostic group. An additional strength of our study is that we normalized whole-brain CBF for brain volume, a significant potential confounder in some previous studies [6] , [11] , [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 2D PC imaging is an accurate and reproducible method to assess whole-brain CBF [10] . Two small studies and one larger study showed that 2D PC imaging is capable of measuring whole-brain CBF, which can be used to differentiate between subjects with SCD and with AD [6] , [11] , [12] . However, those studies did not adjust for brain volume.…”
Section: Introductionmentioning
confidence: 99%